The Effect of Profitability, Financial Leverage, and Accounting Expertise of The Board of Commissioners on Earnings Management - Dwi Marlina Wijayanti (Journal of Accounting Inquiry, 2022)
Purpose: This study examines the impact of profitability, financial leverage, and accounting expertise of the board of commissioners on earnings management practices. Earnings management is a serious problem for some companies with unstable financial conditions. Therefore, it is important to know the factors that can encourage earnings management Methodology: This research is quantitative research. The sample in this study were 92 manufacturing companies listed on the IDX in 2015 – 2019. Data analysis used panel data regression through E-views. Findings: The results of this study indicate that profitability and financial leverage are determinants of earnings management. Other results show that the accounting expertise of the board of commissioners has no effect on earnings management practices. Novelty: Most of the previous research focused on the aspect of the number of the board of commissioners in mitigating earnings management, this study tries to analyze a more specific factor, namely the accounting expertise of the board of commissioners because board members who understand accounting will more easily find errors in financial statement disclosures. Keywords: Leverage, Earnings Management, Profitability, Financial leverage, Accounting Expertise